Fluorescent probe for specific detection of cysteine in the lipid dense region of cells - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Gonnade, Rajesh G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new cysteine (Cys) specific chemodosimetric reagent (ER-F) is used in imaging of endogenous Cys localized in the lipid dense region of the live Hct116 cells and the release of Cys within HepG2 cells from a drug following a biochemical transformation. A silica surface, modified with ER-F, could be used for quantitative estimation of Cys present in aqueous solution (pH 7.2) and in a human blood plasma (HBP).

FRET-based probe for monitoring pH changes in lipid-dense region of Hct116 cells - Reddy, Upendar G.; Anila, H. A.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Organic Letters, 2015)
A rhodamine conjugate (L) with a pseudo Stokes shift of 165 nm is used for probing changes in solution pH under physiological conditions. This reagent is found to be nontoxic, and the luminescence response could be used for imaging changes in endogenous pH induced by dexamethanose (DMT) in the endoplasmic reticulum.

Reagent for specific recognition of cysteine in aqueous buffer and in natural milk: imaging studies, enzymatic reaction and analysis of whey protein - Anila, H. A.; Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
We report a new chemodosimetric probe (L) for specific recognition of cysteine (Cys) in aqueous buffer and in whey protein isolated from fresh cow's milk. Using this reagent we could develop a luminescence-based methodology for estimation of Cys released from a commercially available Cys-supplement drug by aminoacylase-1 in live cells.

Cysteine-specific fluorescent switch for monitoring oxidative stress and quantification of aminoacylase-1 in blood serum - Anila, H. A.; Ali, Firoj; Kushwaha, Shilpi; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Analytical Chemistry, 2016)

Specific receptor for hydrazine: mapping the in situ release of hydrazine in live cells and in an in vitro enzymatic assay - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Mogare, Devraj G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2016)
We report a new chemodosimetric reagent capable of detecting hydrazine in the presence of several other competing amine derivatives and ionic analytes of biological relevance. This reagent has been utilized for real time monitoring of in situ N2H4 release during the metabolism of a crucial tuberculosis drug, isoniazid, in live HepG2 cells. The fluorescence response of the reagent based on its specific reaction with N2H4 is used for developing an in vitro assay for aminoacylase-1.

Specific receptors and imaging reagents for certain heavy metal toxins - Anila, H. A.; Ali, F.; Das, A. (Comprehensive supramolecular chemistry II, 2017)
Among various elements, mercury (Hg) and palladium (Pd) are featured in all lists of heavy metal toxins. Mercury is xenobiotics and toxic even at trace levels of exposure either in elemental (if aerosolized) or in its two ionic forms (viz. Hg(I) and Hg(II)). Importantly, the most common oxidation state of mercury is Hg(II) and this has an appreciably high value for enthalpy of solvation in aqueous media. This fact along with a high spin-orbit coupling constant value are not conducive for designing efficient luminescence ON-based receptors for Hg(II), which are essential for either detection or imaging of such toxins inside the cells or in specific organs. Such sensors have significance in evaluating the influence of such toxins in human physiology as well as in clinical diagnostics. Analogously, Palladium (in oxidation states of 0, II, and IV) is commonly used as a catalyst for the synthesis of various drugs or active pharmaceutical intermediates. Despite best efforts in purification and elimination of palladium used in such reactions, residual concentrations of Pd are often higher than the permissible level set by the World Health Organization. The affinity of Pd toward thiol-containing amino acids, proteins, DNA, or other macromolecules is known to cause physiological disorders. All these necessitate the design and development of efficient imaging reagents that are specific toward a certain cationic analytes and allow for the real-time monitoring for assessing the adverse influences on human physiology. Recent advances in such reagents primarily for Hg(II), Pd(0), and Pd(II) are discussed.

Tracking HOCl concentrations across cellular organelles in real time using a super resolution microscopy probe - Ali, Firoj; Aute, Sunil; Sreedharan, Sreejesh; Anila, H. A.; Saeed, Hiwa K.; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
BODIPY derivative, SF-1, exclusively shows a fluorescence ON response to HOCl and images endogenously generated HOCl in RAW 264.7 macrophages. Widefield and super resolution structured illumination microscopy images confirm localization in the Golgi complex and lysosomes, and hence specifically detects HOCl generated in these organelles. SF-1 is compatible with 3D-SIM imaging of individual cells.